A Comprehensive Systematic Review of Intraoperative Wound Irrigation for The Prevention of Surgical Site Infection after Laparotomy - Satya Agung Nugroho; Fathan Sulistyo Widodo; Hasnan Habib Affifudin (International Medical Journal Corp. Ltd, 2025)
Introduction: Surgical site infections (SSIs) remain a significant complication following laparotomy, leading to increased morbidity, prolonged hospital stays, and higher healthcare costs. Intraoperative wound irrigation (IOWI) has been proposed as a preventive measure, but the optimal solution and technique remain debated. Methods: This systematic review analyzed 40 sources, including randomized controlled trials, meta-analyses, and systematic reviews, retrieved via PubMed, Google Scholar, Semantic Scholar, Springer, Wiley Online Library. Studies were screened based on population (adult laparotomy patients), intervention (IOWI), outcome (SSI incidence), and design (RCTs, meta-analyses). Data extraction was performed using a large language model to capture intervention details, surgical context, SSI definitions, outcomes, and effect measures. Results: IOWI significantly reduces SSI rates compared to no irrigation (RR 0.52, 95% CI 0.37–0.74). Antiseptic solutions, particularly povidone-iodine and polyhexanide, may offer additional benefit over saline in certain contexts, though evidence is heterogeneous. Antibiotic irrigation shows strong benefits in contaminated wounds and colorectal surgery. Pulse lavage is superior to standard pouring, while excessive irrigation volume may be counterproductive. Discussion: The efficacy of IOWI is highly context-dependent, influenced by surgical type, contamination level, irrigation technique, and study quality. Antiseptic and antibiotic irrigations are most beneficial in high-risk settings, whereas saline irrigation remains effective in clean-contaminated cases. Conclusion: Routine IOWI before skin closure is recommended for laparotomy patients. Antiseptic or antibiotic solutions should be considered in contaminated or colorectal surgery, and pulse lavage may enhance effectiveness. Future research should standardize protocols and focus on high-risk populations.